High-throughput screening system of citrus bacterial canker-associated transcription factors and its application to the regulation of citrus canker resistance - Jia Fu; Jie Fan; Chenxi Zhang; Yongyao Fu; Baohang Xian; Qiyuan Yu; Xin Huang; Wen Yang; Shanchun Chen; Yongrui He; Qiang Li (Journal of Integrative Agriculture, 2024)
One of the main diseases that adversely impacts the global citrus industry is citrus bacterial canker (CBC), caused by the bacteria Xanthomonas citri subsp. citri (Xcc). Response to CBC is a complex process, with both protein-DNA as well as protein–protein interactions for the regulatory network. To detect such interactions in CBC resistant regulation, a citrus high-throughput screening system with 203 CBC-inducible transcription factors (TFs), were developed. Screening the upstream regulators of target by yeast-one hybrid (Y1H) methods was also performed. A regulatory module of CBC resistance was identified based on this system. One TF (CsDOF5.8) was explored due to its interactions with the 1-kb promoter fragment of CsPrx25, a resistant gene of CBC involved in reactive oxygen species (ROS) homeostasis regulation. Electrophoretic mobility shift assay (EMSA), dual-LUC assays, as well as transient overexpression of CsDOF5.8, further validated the interactions and transcriptional regulation. The CsDOF5.8–CsPrx25 promoter interaction revealed a complex pathway that governs the regulation of CBC resistance via H2O2 homeostasis. The high-throughput Y1H/Y2H screening system could be an efficient tool for studying regulatory pathways or network of CBC resistance regulation. In addition, it could highlight the potential of these candidate genes as targets for efforts to breed CBC-resistant citrus varieties.